A mixed-method of the happy-productive: wellbeing and performance patterns of remote workers in Brazil - Pérez-Nebra, Amalia Raquel; Villajos, Esther; Peñalver, Jonathan (Frontiers in Sociology, 2025)
The present study aims to examine the relationship between job wellbeing (emotions at work) and job performance (in-role, extra-role) and their connection in remote work using open questions. The sample consists of 297 Brazilian remote workers. Using a mixed-method approach, the findings reveal a 4-cluster pattern associated with the relationship between job wellbeing and job performance (i.e., 9-to-5, entrenched, engaged, and burned-out). Moreover, only high-performance patterns showed a relationship with the four categories of issues associated with remote work. Some issues are transversal to all groups, such as the Trade-off experience and the Adaptability process. However, Social exchange is only important for the entrenched pattern and the Lack of social resources is only linked to the engaged pattern.